TINJAUAN YURIDIS SENGKETA KONSUMEN DALAM PEMBIAYAAN MOBIL PADA PT ADIRA DINAMIKA MULTI FINANCE (STUDI PUTUSAN No. 83/PDT.SUS.BPSK/2022/PN.PDG) - Yenni Fitria; Devirianti Effendi; Ridwan Wijaya (Ensiklopedia of Journal, 2023)
Industrialization and globalization on the one hand have had a positive impact by providing many choices of goods and/or services for consumers publicprotect the interests of consumers, in addition to what has been regulated in Law no. 8 of 1999 concerning Consumer Protection (UUPK) as a legal umbrella for consumer protection in Indonesia. The research is descriptive in nature, namely research that provides an overview of the dispute process faced by consumers with PT. Adira Dinamika Multi Finance. To obtain the desired data and to obtain satisfactory results, the author uses a juridical approach. From the legal considerations of the judges above, it can be concluded that there was a mistake in the legal considerations of the panel of judges who examined case no.83/Pdt.Sus.BPSK/2022/PN.PDG,which also has legal consequences for the Respondent's Objection, where in Article 1 paragraph 2 of Law Number 48 of 2009, concerning Consumer Protection. Judicially, the interests of the Respondent have also been set aside by the panel of judges examining the aquo case. And according to the author's opinion, the beginning of all disputes between Business Actors or Financing Institutions (leasing), that the existing agreement between Business Actors and Consumers constitutesA standard agreement in which there are certain conditions made by the business actor, without involving the consumer in drafting the contract, so that the consumer has no other choice, and under his control, the panel of judges should not only see the delay in the Respondent's Objection, but how a this agreement.Keywords: Consumer Protection, Financing Institutions.